Implementation of the Advanced Encryption Standard (AES) Cryptographic Algorithm in Library Information Systems for Member Data Security at the Cipanas Presidential Palace - Putri Maharani; Jusmardi Jusmardi; Ahmaddul Hadi; Melri Deswina (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study aims to develop a data security system for the Pancadaya Waste Bank web-based application by implementing a hybrid cryptography algorithm combining AES and RSA. The main problem identified is the vulnerability of manually recorded and unsecured transaction data. The research applied a qualitative approach through interviews with system users and the Environmental Agency, as well as literature reviews on hybrid cryptography algorithms. The system was developed using the Rapid Application Development (RAD) method and implemented using PHP, MySQL, and the OpenSSL library. The results show that the system successfully encrypts transaction data using AES and secures the AES key with RSA, thereby enhancing data security. Testing with GTmetrix indicates excellent application performance. Furthermore, the system can display and decrypt real-time transaction data in receipt form for both deposit and withdrawal processes. This application provides an innovative solution to data management and transaction security issues in digital-based waste bank systems.